Solitons & polarons in conducting polymers - Yu, Lu. (World Scientific, 1988)
The main purpose of this volume is to provide the newcomer to this exciting field with a detailed introduction to basic concepts along with a collection of selected original papers. The selection is inevitably subjective,...